Analisis Tokoh, Peran, dan Karakteristik Naskah dalam Drama Monolog Aeng karya Putu Wijaya - Dhea Nur Aini; M Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2021)
This study aims to describe the elements of character, role, and character in Putu Wijaya's monologue drama script. This type of research is qualitative research using descriptive methods. The data in this study are the sentences and utterances of the characters or narrators. The research stages were carried out in the following steps: (1) reading and understanding the drama script of Putu Wijaya's monologue Aeng; (2) literature study related to the matters under study in order to obtain an understanding of the problem to be studied and (3) to take inventory of data. After the data has been collected, it is analyzed using the following steps: (1) classifying the data; (2) interpret data; (3) draw conclusions; and (4) reporting the results of data analysis. Based on the results of data analysis, it can be concluded, namely: (1) the characters in the monologue drama script of Aeng by Putu Wijaya, the characters contained in this monologue drama script are Alimin, Nensi, Hakim, Bapak, Karpo, Ibu, and Bastard; Besides that, it is also found the role of characters in the drama script of Aeng's monologue by Putu Wijaya about the roles of lion, mars, sun, earth, scale, and moon; (2) the character of a character can be seen based on three aspects, namely physiological aspects, sociological aspects and psychological aspects.